Nurtureshock : new thinking about children - Bronson, Po, 1964- (Twelve, 2009)
Award-winning science journalists Po Bronson and Ashley Merryman demonstrate that many of modern society's strategies for nurturing children are in fact backfiring, because key twists in the science of child development have been overlooked. The authors discuss the inverse power of praise, why insufficient sleep adversely affects kids' capacity to learn, why white parents don't talk about race, why kids lie, why evaluation methods for "giftedness" and accompanying programs don't work, and why siblings really fight.